A study on the prevalence of smoking habits among the student community in Aseer Region, Saudi Arabia - Kandasamy, Geetha; Sam, Gigi; Almanasef, Mona; Almeleebia, Tahani; Shorog, Eman; Alshahrani, Asma M.; Almohaimeed, Rana A.; Hmlan, Amjad; Al Suhaym, Atheer Y.; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy; et al. (Frontiers in Public Health, 2023)
Objectives A cross-sectional study was aimed to assess the prevalence of smoking habits among students at King Khalid University (KKU), Abha, KSA. Methods This was a cross-sectional study using a Modified Fagerstrom Tolerance Questionnaire (mFTQ), online survey was carried out among the students of KKU. This tool uses a five-point Likert scale for all seven questions, except one question on smoking during the first 2 h of the day. Results The prevalence of smoking among male students was 67% (n = 243) and females 33% (n = 122). Of the current cigarette smokers, 19% had a nicotine dependence score of ≥6 (high), 48% scored 4–6 (moderate) and 33% scored <4 (minimal). Association between mFTQ and the number of cigarettes per day (p < 0.001), first smoke of your cigarettes (p < 0.018), smoking in the morning (p < 0.007), and difficulty refraining from smoking in public areas (p < 0.000). The results of the current study recommend that cigarette smoking habits are a significant risk behavior among young students. The strength of this study signifies that most participants (62%) intend to quit if appropriately supported. Conclusion According to the findings of the current investigation, smoking was quite common among males. It raises the alarm about the critical need for adequate education to support health education initiatives, discourage teen smoking, and enhance health outcomes for the community.